PENINGKATAN KEMAMPUAN PENALARAN DAN BERPIKIR KREATIF MATEMATIS SERTA PENCAPAIAN SELF-DETERMINATION SISWA MELALUI STRATEGI MCREST - Nurfadilah Siregar, - (2018)
Penelitianinisecaraumumbertujuanuntukmengkajipeningkatankemampuanpenalaranmatematis (PM) danberpikirkreatifmatematis (BK), sertapencapaianself-determination (SDT) siswamelaluistrategimeaningfulness, confidence, relevance, enjoyment, social relationships, targets(MCREST) yang selanjutnya disebut sebagai PMT danpembelajaranlangsung (PL) berdasarkanpembelajaran, level sekolah, dankemampuanawalmatematis (KAM). Metodepenelitianiniadalaheksperimensemudenganmenggunakannonequivalent control-group design.Populasidalampenelitianiniadalahsiswakelas VIII SMPN di Kota Cimahi yang menerapkanKurikulum 2013 padaTahunAjaran 2016/2017.Sampeldalampenelitianiniadalahsiswapadaduakelas di setiap level sekolahberbeda yang keseluruhannyaberjumlah 122 orang siswa. Instrumen yang digunakanterdiridarisoaltes PM dan BK, sertaskala SDT. Dari penelitianinikesimpulan yang diperolehadalah: (1) Secarakeseluruhantidakterdapatperbedaanpeningkatan PM, BK, sertapencapaian SDT siswa yang mengikuti PMT dansiswa yang mengikuti PL; (2) berdasarkan level sekolah, pada level sekolahtinggi, peningkatan PM siswa yang mengikuti PMT lebihbaikdaripadasiswa yang mengikuti PL, sedangkanpeningkatan BK danpencapaian SDT siswa yang mengikuti PMT tidaklebihbaikdaripadasiswa yang mengikuti PL, pada level sekolahsedang, tidakterdapatperbedaanpeningkatan PM dan BK, sertapencapaian SDT siswa yang mengikuti PMT dansiswa yang mengikuti PL; (3) berdasarkankategori KAM, pada KAM tinggi, peningkatan PM siswa yang mengikuti PMT lebihbaikdaripadasiswa yang mengikuti PL, sedangkanpeningkatan BK danpencapaian SDT siswa yang mengikuti PMT tidaklebihbaikdaripadasiswa yang mengikuti PL, pada KAM sedangdan KAM rendah, tidakterdapatperbedaanpeningkatan PM dan BK, sertapencapaian SDT siswa yang mengikuti PMT dansiswa yang mengikuti PL; (4) Terdapatpengaruhinteraksiantarapembelajarandan level sekolahterhadappeningkatan PM, sedangkanpadakemampuanlainnyayakni BK dan SDT, tidakterdapatpengaruhinteraksiantarapembelajarandan level sekolahterhadappeningkatan BK ataupunpencapaian SDT; (5) Terdapatpengaruhinteraksiantarapembelajarandankemampuanawalmatematisterhadappeningkatan PM, sedangkanpadakemampuanlainnyayakni BK dan SDT, tidakterdapatpengaruhinteraksiantarapembelajarandankategori KAM terhadappeningkatan BK ataupunpencapaian SD;---In general, the purpose of this study is to analyze the enhancement of students' mathematical reasoning and creative thinking ability, and their achievement in self-determination through meaningfulness, confidence, relevance, enjoyment, social relationships, targets (MST) strategy and direct learning (DL) based on learning strategy, school level, and mathematical prior knowledge. In this study, research method is quasi experiment that used nonequivalent control-group design. The population in this study was the students in Grade VIII in Cimahi City which implemented Kurikulum 2013 in School Year 2016/2017. The samples were taken from different classes and school level, the total number of the samples were 122 students. The instruments in this study consists of eight essay test of mathematical reasoning and six essay test of mathematical creative thinking, and 40 items scale in self-determination. The conclusion of this study are: (1) There are no difference enhancement of students mathematical reasoning and creative thinking ability, achievement in self-determination in MST and DL; (2) Based on school level, in high school level, the enhancement of students mathematical reasoning ability in MST is better than the enhancement of students mathematical reasoning ability in DL, but for the enhancement of mathematical creative thinking ability and their achievement in self-determination are no differences in MST and DL, in middle school level, the enhancement of students mathematical reasoning and creative thinking ability, and their achievement in self-determination are no differences in MST and DL; (3) Based on mathematical prior knowledge categories, in high mathematical prior knowledge, the enhancement of students mathematical reasoning ability in MST is better than the enhancement of students mathematical reasoning ability in DL, but there are no differences in terms of the enhancement of students mathematical creative thinking ability and their achievement in self-determination in MST and DL, in other groups of mathematical prior knowledge, the enhancement of students mathematical reasoning and creative thinking ability, and their achievement in self-determination are no differences in MST and DL; (4) There exist an interaction effect between learning strategy and school level towards the enhancement of mathematical reasoning ability whereas between the enhancement of mathematical creative thinking ability as well as the achievement in self-determination, there is no interaction effect; (5) There exist an interaction effect between learning strategy and mathematical prior knowledge towards the enhancement of mathematical reasoning ability whereas between the enhancement of mathematical creative thinking ability as well as the achievement in self-determination, there is no interaction effect.